APPLICATION OF GRAVITY METHOD TO ESTIMATE CO2 INJECTION VOLUME OF NGRAYONG FORMATION - TIRZA AZKA SYAVIENDY (NIM: 12313067), AVINSKA
Carbon dioxide (CO2) is a greenhouse gas that contributes to EarthÃ‚Â’s global warming. Over the past two centuries, its concentration in the atmosphere has greatly increased, mainly because of human activities such as fossil fuel burning. One feasible option for reducing CO2 emissions is to store it underground. This technique is called Carbon dioxide Capture and Storage (CCS). This technique could be applied to emissions from large power plants or industrial facilities. The process involves three main steps. The first step is to capture CO2 at its source by separating it from other gases produced by an industrial process. The second step is to transport the compressed CO2 to a suitable storage location, typically in compressed form, and the last step is to store the CO2 away from the atmosphere for a long period of time, for instance in an underground geological formation. CCS development in Indonesia is increasing rapidly, one of the research area is Gundih Field, located in East Java. Targeted geological formation which acts as a reservoir is Ngrayong Formation. The data used in this research is obtained from gravity data acquisitionconducted in September 2014 at Gundih Field. Data processing is carried to obtain Complete Bouguer Anomaly. This process is followed by separating regional and residual gravity anomaly using Moving Average method. Forward Modeling 2.5D is done based on additional informations. Pseudo-3D Modeling is done in order to visualize subsurface geological conditions. This process enables us to estimate the volume of Ngrayong Formation. The estimated volume of Ngrayong Formation is 17,168 x 1012 m3 and the estimated volume of Ngrayong Formation that is capable of being injected by CO2 is 120,176 x 109 m3.